2020
DOI: 10.3390/jcm10010043
|View full text |Cite
|
Sign up to set email alerts
|

Urinary NGAL Measured after the First Year Post Kidney Transplantation Predicts Changes in Glomerular Filtration over One-Year Follow-Up

Abstract: Currently, serum creatinine and estimated glomerular filtration rate (eGFR) together with albuminuria or proteinuria are laboratory markers used in long-term monitoring of kidney transplant recipients. There is a need for more sensitive markers that could serve as early warning signs of graft dysfunction. Our aim was to assess the urinary concentrations of neutrophil gelatinase-associated lipocalin (NGAL) as a predictor of changes in kidney transplant function after the first year post-transplantation. We pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 59 publications
(94 reference statements)
0
13
0
1
Order By: Relevance
“…The exclusion criteria were: acute kidney injury defined according the KDIGO 2011 [ 25 ], any condition requiring hospital treatment during three months before the recruitment, and signs or symptoms of any infection (including urinary tract infection) at the time of recruitment. The present study included a subset of a larger group described previously [ 26 ]; the measurements of serum sCD93 were performed in the sera of the first 78 patients recruited.…”
Section: Methodsmentioning
confidence: 99%
“…The exclusion criteria were: acute kidney injury defined according the KDIGO 2011 [ 25 ], any condition requiring hospital treatment during three months before the recruitment, and signs or symptoms of any infection (including urinary tract infection) at the time of recruitment. The present study included a subset of a larger group described previously [ 26 ]; the measurements of serum sCD93 were performed in the sera of the first 78 patients recruited.…”
Section: Methodsmentioning
confidence: 99%
“…Trailin et al were able to show that high levels of interleukin 2 in urine are associated with worsened eGFR ( 6 ). Kielar et al showed that elevated neutrophil gelatinase-associated lipocalin (NGAL) levels in the urine were associated with an eGFR loss after transplantation ( 7 ). However, sufficient biomarkers to obtain robust and validated information about long-term allograft function and to identify patients at risk, are still lacking today.…”
Section: Introductionmentioning
confidence: 99%
“…Heyne et al [ 24 ], studying uNGAL in 182 outpatient renal allotransplant recipients on maintenance immunosuppression, noted that determination of urinary NGAL levels could be a parameter to differentiate acute allotransplant rejection from other causes of AKI in follow-up after kidney transplantation. Kielar et al [ 38 ], performing a study on 109 kidney recipients with stable transplant function one year after transplantation, found that uNGAL and sNGAL and NGAL/creatinine can be used to estimate the change in kidney transplant function.…”
Section: Biomarkers Of Allogeneic Kidney Transplant Rejectionmentioning
confidence: 99%